Chemical variables - stream from Följemaden, outlet-stream-4, 2014-04-09–2018-05-15 - Skogaryd Research Catchment (University of Gothenburg, 2026)
Manual grab samples from the stream for chemical analysis are taken on a biweekly basis during ice-free conditions, and on a monthly basis in the presence of stream ice.
Skogaryd Research Catchment (2026). Chemical variables - stream from Följemaden, outlet-stream-4, 2014-04-09–2018-05-15 [Data set]. Swedish Infrastructure for Ecosystem Science (SITES). https://hdl.handle.net/11676.1/l7ezbouBsuyXWCTZUhh9Hp0E
Keywords: Skogaryd Research Catchment; Stream; Time instant; Time instant; pH; pH; Electrical conductivity; Electrical conductivity; Water temperature; Water temperature; Dissolved organic carbon; Dissolved organic carbon; Total nitrogen; Total nitrogen; Phosphate-P; Phosphate-P; Ammonium-N; Ammonium-N; Nitrate-N; Nitrate-N; Sulphate-S; Sulphate-S; Fluorine; Fluorine; Chlorine; Chlorine; Aluminium; Aluminium; Boron; Boron; Calcium; Calcium; Iron; Iron; Potassium; Potassium; Magnesium; Magnesium; Manganese; Manganese; Sodium; Sodium; Phosphorus; Phosphorus; Sulfur; Sulfur; Silicon; Silicon; Zinc; Zinc; Lithium; Lithium; Beryllium; Beryllium; Vanadium; Vanadium; Chromium; Chromium; Cobalt; Cobalt; Nickel; Nickel; Copper; Copper; Gallium; Gallium; Arsenic; Arsenic; Selenium; Selenium; Rubidium; Rubidium; Cadmium; Cadmium; Tellurium; Tellurium; Caesium; Caesium; Barium; Barium; Thallium; Thallium; Lead; Lead; Bismuth; Bismuth; Absorbance; Absorbance; Soil Science; Markvetenskap; Agriculture, Forestry and Fisheries; Jordbruk, skogsbruk och fiske; Agricultural Science; Jordbruksvetenskap; Ecology; Ekologi; Multidisciplinary Geosciences; Multidisciplinär geovetenskap; Environmental Sciences; Miljövetenskap